THE EMPATHY PARADOX: UNCOVERING THE PHENOMENON OF BULLYING IN THE HEALTHCARE WORLD - Navira, Afifah; Tania, Nurul; Ramadhani, Wusti Alya; Tinambunan, Joice; Soufyan, Ridho Abrar; Yunita, Sri (LPPM Univ. Ibn Khaldun Bogor, 2025)
The phenomenon of workplace bullying, particularly in the health or medical field, presents an irony. A profession that should be synonymous with empathy, care, and respect for human values has instead become a place with high levels of abusive behavior in various countries. This study aims to uncover the empathy paradox in the healthcare profession by analyzing the causes, forms, and impacts of bullying, while also offering a conceptual basis for systemic prevention strategies. This study uses qualitative methods with a literature review to explore the dynamics of the empathy paradox. The results show that bullying does not only arise because someone fails to manage their emotions, but also occurs because there is a system that allows for abusive and oppressive behavior. The most effective solution to overcome this problem is to create policies that do not tolerate bullying at all, strengthen a secure reporting system, implement empathetic leadership, and reform a healthy work culture. These steps are crucial to ensure that empathy is truly implemented, not only in the relationship between healthcare workers and patients but also in interactions among healthcare professionals